P092: Exercise prescription in the emergency department: patient perceptions. (15th May 2017) - Milne, F.; Leech-Porter, K.; Lewis, D.; Fraser, J.; Hull, S.; Atkinson, P.R.
Abstract : Introduction: The positive health outcomes of exercise have been well-studied, and exercise prescription has been shown to reduce morbidity in several chronic health conditions. However, patient attitudes around the prescription of exercise in the emergency department (ED) have not been explored. The aim of our pilot study is to explore patients' willingness and perceptions of exercise being discussed and prescribed in the ED.Methods: This study is a survey of patients who had been previously selected for exercise prescription in a pilot study conducted at a tertiary care ED. This intervention group were given a standardized provincial written prescription to perform moderate exercise for 150 minutes per week. Participants answered a discharge questionnaire and were followed up by a telephone interview 2 months later. A structured interview of opinions around exercise prescription was conducted. Questions included a combination of non-closed style interview questions and Likert scale. Patients rated prescription detail, helpfulness and likelihood on a Likert scale from 1-5 (1 being strongly disagree and 5 being strongly agree). Median values (+/-IQRs) are presented, along with dominant themes.Results: 17 people consented to exercise prescription and follow up surveys. 2 were excluded due to hospital admission. 15 participants were enrolled and completed the discharge survey. Two-month follow up survey response rate was 80%. Patients rated the detail given in their prescription as 5 (+/-1). Helpfulness of prescription was rated as 4 (+/-2). Likelihood to continue exercising based on the prescription was rated as 4 (+/-2). 11/12 participants felt that exercise should be discussed in the Emergency Department either routinely or on a case-by-case basis.1 participant felt it should not be discussed at all.Conclusion: Our study demonstrates that most patients are open to exercise being discussed during their Emergency Department visit, and that the prescription format was well-received by study participants.